The Californiacs - Gillmore, Inez Haynes, 1873-1970 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Californiacs" by Inez Haynes Gillmore is a witty and engaging examination of California's distinctive cultural identity, written in the early 20th century. This insightful narrative blends elements of travel writing and social commentary, capturing the quirks and attitudes of Californians, whom the author hilariously dubs "Californiacs". The book appears to explore themes of regional pride, insularity, and the perception of beauty, offering a satirical yet affectionate portrayal of those who inhabit this vibrant state. In her writing, Gillmore humorously critiques the self-importance and insular attitudes of Californiacs, who exhibit a fervent pride in their state's scenic beauty and cultural successes. The narrative features a range of characters, including both natives and newcomers to California, illustrating their amusing and often exaggerated comparisons to the East. The author's experiences in California reveal the contrast between what she appreciates about her New England roots and the overwhelming Californian perspective that beauty and greatness are exclusive to their homeland. Through vivid descriptions and humorous anecdotes, "The Californiacs" presents a rich tapestry of Californian life, showcasing the state as a place of beauty, creativity, and a unique spirit that captivates both its residents and visitors alike. (This is an automatically generated summary.)
Release date is 2002-07-01
Produced by David A. Schwan, and David Widger
Keywords: California -- Description and travel